Hadley Cell Edge Modulates the Role of Ekman Heat Flux in a Future Climate. Issue 17 (9th September 2022) - Hasan, Mahdi; Larson, Sarah; McMonigal, Kay
Abstract: In a future climate, the Hadley cell and associated trade easterlies are projected to expand poleward. This projected change in the atmospheric circulation is expected to impact the ocean through changes in the mean sea surface temperature (SST). We also expect implications for the large‐scale SST variability, because near‐surface wind is directly related to two drivers of the SST, that is, turbulent heat flux and anomalous wind‐driven Ekman heat flux. Previous studies show that in the subtropics, anomalous turbulent and Ekman heat fluxes oppose each other, acting to reduce SST variability, whereas, in the midlatitudes, they reinforce each other and enhance SST variability. Through analysis of reanalysis products and Coupled Model Intercomparison Project simulations, we find that the subtropical regions where the fluxes oppose each other are projected to expand poleward in a future climate, following the poleward expansion of the Hadley cell, with potential implications for the amplitude of subtropical SST variability. Plain Language Summary: Atmospheric surface wind drives upper ocean circulations. Hence, a change in the surface wind pattern causes a change in ocean circulation. There is evidence that climate change alters the spatial pattern and strength of the surface winds. In particular, easterly winds in the subtropics are projected to expand poleward. The poleward shift of the easterly wind belt also has potential implications for the sea surface temperature (SST) variations because two important drivers of the SST are related to the surface wind: air‐sea heat exchange and the advection of ocean temperature by the wind‐driven ocean current. In the subtropical region, these two mechanisms typically oppose each other, acting to reduce the amplitude of SST variations. We show that the projected poleward expansion of the easterly wind belt will subsequently expand the subtropical region where these two mechanisms oppose each other toward the poles, with potential implications for subtropical SST variability. Key Points: Anomalous Ekman heat flux opposes and reinforces the anomalous turbulent heat flux in the subtropics and midlatitudes, respectively The latitudinal boundary where the role of anomalous Ekman heat flux changes is modulated by the Hadley cell edge A poleward shift of the Hadley boundary in a future climate drives a poleward shift in the latitude where Ekman heat flux changes its role